Penggunaan Earplugs dan Eye Masks untuk Meningkatkan Kualitas Tidur Pasien di ICU - Ainnur Rahmanti; Dwi Mulianda (Jurnal Kesehatan Komunitas, 2022)
Sleep is an important step in the recovery process of patients in the ICU. Poor sleep quality is one of the events that prolongs the patient's stay in the ICU. Sleep disturbances in critically ill patients occur from the initial phase of treatment to the late stages of recovery for more than two decades. The causes of disturbances in the quality and quantity of sleep in critically ill patients are the patient's own illness, the effects of drugs, psychological factors, the environment, namely noise, lighting, patient and provider interactions. health services and treatment procedures. This study aimed to identify the difference of sleep quality on patients in the ICU after using earplugs and eyemasks. This study was quasi experiment study with nonequivalent control group design. Respondents in this study amounted to 15 patients treated in the ICU obtained from 30 samples of patients. This study states that 10-17% of the noise in the intensive care unit is at a level that causes patients to wake up and wake up from their sleep, namely the noise reaches 70dB and is mostly caused by communication between staff and patients or with others as well as television. The noise experienced by the patient can come from the bedsite monitor alarm, the infusion/syringe pump alarm, pulse oximetry, the voice of the officer's telephone, television, room telephone and ventilator alarm. The provision of a combination earplug and eye mask intervention to improve the quality of sleep of patients in the intensive room of Bhakti Wira Tamtama Hospital Semarang proved to be very significant, with a p value of 0.000. Recommendations for further research are that more in-depth interventions can be carried out by paying attention to other factors, namely the patient's condition, giving nursing interventions at night to the use of medications that affect the quality of sleep of patients in the intensive care unit.